2005
DOI: 10.1001/archinte.165.19.2272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Clinical Trial Alert System on Physician Participation in Trial Recruitment

Abstract: Use of an EHR-based CTA led to significant increases in physicians' participation in and recruitment rates to an ongoing clinical trial. Given the trend toward the EHR implementation in health care centers engaged in clinical research, this approach may represent a much-needed solution to the common problem of inadequate trial recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(148 citation statements)
references
References 28 publications
4
141
0
Order By: Relevance
“…The work in [12,13] presented a clinical trial alert system for a single clinical trial at a US academic healthcare system. The clinical trial was on diabetes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The work in [12,13] presented a clinical trial alert system for a single clinical trial at a US academic healthcare system. The clinical trial was on diabetes.…”
Section: Related Workmentioning
confidence: 99%
“…MEANS is a tool which helps physicians to find eligible patients for their trials, in the case where a patient is found to be ineligible by MEANS, they would also have their case reviewed by a physician-investigator. From the results of the clinical trial alert system [13], we are encouraged to believe that many patients can be automatically ruled out in a timely manner. Depending on the acceptable time frame only about 20% would need further investigation.…”
Section: Additional Streamlining Of the Processmentioning
confidence: 99%
“…While some additional realworld uses of EHR's, such as integrated scheduling of research participant visits and sharing of real-time data on research progress, are likely to be limited by human research protection requirements, the four advantages listed in Table 1 still offer powerful tools for clinical translational research. While some researchers have used EHR resources in their work [23][24][25][26][27], such use of the EHR is in its infancy, and relatively little has been written about how to implement it effectively. Relevant questions that need to be addressed include: What are the challenges that need to be overcome (human, technological, organizational, and financial)?…”
Section: Introductionmentioning
confidence: 99%
“…A key deterrent to participation is that matching patients to clinical trials is currently a manual, physician-driven process. Automating this process has shown some promising results in terms of increased patient referrals from physicians [2]. However, current efforts at automation require the development of custom applications.…”
Section: Introductionmentioning
confidence: 99%